Multifunctional resin adhesive film with high magnetic particle content as well as preparation method and application of multifunctional resin adhesive film
By adding high-magnetic particles to the resin film through the glue filtering and glue-absorbing method, combined with the structural characteristics of the fiber membrane, the problem of difficulty in forming a resin film with a high magnetic particle content was solved, and the preparation and production of a high-content magnetic particle resin film was achieved. Increased versatility.
Patent Information
- Application Number
- CN202411459606.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, it is difficult to prepare resin films with high magnetic particle content, especially while maintaining wave absorption properties, the increase in the content of magnetic particles leads to an increase in viscosity and making film difficult.
The resin glue film with high magnetic particle content is prepared by using the filter glue absorbing method. By attaching the filter glue layer to the absorbing layer, the porosity and thickness-to-diameter ratio of the fiber membrane are used to control the viscosity of the resin and the distribution of magnetic particles to achieve high Preparation of resin film containing magnetic particles.
Realize the preparation of high magnetic particles content resin glue film, with excellent absorption performance, and have multifunctional properties such as toughened, self -unveiling, lightning protection, conductivity, and high shielding. Essence
Smart Images

Figure CN119329163A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of structural and functional integrated composite materials, and in particular to a multifunctional resin film with high magnetic particle content, a preparation method and an application thereof. Background Art
[0002] Magnetic loss type absorbing materials are an important type of electromagnetic wave absorbing materials with high magnetic permeability. Common magnetic loss type absorbing materials include carbonyl iron powder, ferroferric oxide, ferrite, etc. Magnetic loss type absorbing materials have advantages in broadening low-frequency absorption and are often used as magnetic absorption layer materials. For example, resin films containing magnetic particles are widely used in absorbing structural parts.
[0003] The wave-absorbing performance of the material is related to the loading of magnetic particles. In order to achieve the purpose of weight reduction, it is necessary to increase the content of magnetic particles as much as possible while maintaining wetting, thereby reducing the amount of resin components. However, when the content of magnetic materials increases to a certain value, such as after the volume fraction reaches 42%, the viscosity of the wave-absorbing resin containing magnetic particles increases rapidly, making it difficult to form a film using conventional methods, especially for resins mixed with flaky magnetic materials. Therefore, how to prepare a resin film with a high content of magnetic materials has become a technical problem. Summary of the invention
[0004] The present invention mainly aims at the above problems. In order to solve the problem of preparing resin films with high magnetic particle content, a filter and glue suction method is proposed to prepare resin films with high magnetic particle content. Moreover, this method enables the material to obtain other functions on the basis of magnetic loss and wave absorption function, such as toughening, self-peeling film, lightning protection, conductivity, high shielding and other functions.
[0005] The present invention protects a multifunctional high magnetic particle content resin film and a preparation method thereof, which can be used to prepare a multifunctional high magnetic particle content resin film with excellent wave absorbing performance. The magnetic resin film can be further used for a multifunctional composite material.
[0006] The technical solution of the present invention is implemented as follows: the present invention provides a multifunctional resin film with a high magnetic particle content, wherein the multifunctional resin film with a high magnetic particle content comprises an absorbing layer and a filter layer attached to the surface of the absorbing layer;
[0007] The wave absorbing layer is a film containing highly magnetic particles;
[0008] The filter layer is selected from fiber membrane I and / or fiber membrane II-functional membrane;
[0009] The functional membrane in the fiber membrane II-functional membrane covers the fiber membrane II;
[0010] The volume percentage of magnetic particles in the multifunctional resin film with high magnetic particle content is 40-75%.
[0011] Optionally, the volume percentage of the magnetic particles in the multifunctional high magnetic particle content resin film is independently selected from any value of 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or a range between any two of the above.
[0012] Optionally, the pure resin in the multifunctional high magnetic particle content resin film is selected from at least one of epoxy resin and bismaleimide resin;
[0013] The thickness of the fiber membrane I is 5 to 200 μm;
[0014] The fiber membrane I has a thickness-to-diameter ratio of ≥10 and a porosity of greater than 40%.
[0015] Optionally, the thickness of the fiber membrane I is independently selected from any value among 5 μm, 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm or a range value between any two of the above.
[0016] Optionally, the thickness of the fiber membrane II in the fiber membrane II-functional membrane is 1 to 200 μm;
[0017] The thickness of the fiber membrane II in the fiber membrane II-functional membrane is 5 to 50 μm;
[0018] The fiber diameter of the fiber membrane II is ≤5 μm;
[0019] The fiber membrane I and fiber membrane II are independently selected from at least one of carbon nanotube membrane, carbon nanofiber membrane, high-toughened nano non-woven fabric, high-toughened melt-blown fabric, and melt-blown micron fiber membrane.
[0020] Optionally, the thickness of the fiber membrane II in the fiber membrane II-functional membrane is independently selected from any value of 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm or a range between any two of the above values.
[0021] Optionally, the functional membrane in the fiber membrane II-functional membrane is selected from at least one of a metal-plated non-woven fabric, a smooth film containing holes, and a porous resistor film;
[0022] The functional membrane is a metal-plated non-woven fabric with a surface resistance of ≤0.05Ω, a thickness of 10 to 100 μm, and a pore size of less than 20 μm;
[0023] The functional film is a smooth film containing holes, and the diameter of the holes is ≤2mm;
[0024] The functional film is a porous resistor film with a thickness of 5 to 100 μm.
[0025] Optionally, the functional film is a porous resistive film, and the thickness is independently selected from any value among 5 μm, 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, or a range between any two of the above values.
[0026] According to another aspect of the present application, a method for preparing the above-mentioned multifunctional resin film with high magnetic particle content is provided, the preparation method comprising:
[0027] The low magnetic particle resin film is sequentially attached to the filter layer and the adhesive absorption layer, and then adhesive absorption is performed. After the adhesive absorption is completed, the adhesive absorption layer is removed to obtain a multifunctional resin film with high magnetic particle content.
[0028] Optionally, the volume percentage of magnetic particles in the low magnetic particle resin film is 30-40%;
[0029] The thickness of the low magnetic particle resin film is less than 1.5 mm;
[0030] The magnetic particles in the low-magnetic particle resin film are selected from flaky carbonyl iron powder and / or spherical carbonyl iron powder.
[0031] Optionally, the volume percentage of the magnetic particles in the low magnetic particle resin film is independently selected from any value of 30%, 32%, 34%, 35%, 36%, 38%, 40% or a range between any two of the above.
[0032] Optionally, the adhesive absorbing layer is selected from at least one of organic fiber felt, glass fiber cloth, and breathable release cloth;
[0033] The thickness of the adhesive absorbing layer is 100-700 μm.
[0034] Optionally, the thickness of the adhesive absorbing layer is independently selected from any value of 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm or a range between any two of the above values.
[0035] Optionally, when the adhesive absorption layer is selected from plain glass fiber cloth and / or breathable demoulding cloth, after the low-magnetic particle resin film is sequentially bonded to the adhesive filter layer and the adhesive absorption layer, the steps of adhesive absorption and removal of the adhesive absorption layer are omitted, and the adhesive absorption layer is directly used for laying and co-curing together with the prepreg of the composite material. After curing and molding, the co-cured adhesive absorption layer is torn off through the interlayer separation.
[0036] Optionally, during the glue suction, the viscosity of the pure resin in the low magnetic particle resin film at the glue suction temperature is lower than 40 Pa.s;
[0037] The pressure of the glue suction is 0.04-1MPa;
[0038] The time of the glue suction is 1 to 60 minutes.
[0039] Optionally, the glue suction pressure is independently selected from any value among 0.04MPa, 0.05MPa, 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.8MPa, 1MPa or a range between any two of the above values.
[0040] Optionally, the adhesive absorbing layer is removed by peeling off the adhesive absorbing layer with a film peeling machine.
[0041] According to another aspect of the present application, there is provided a use of the above-mentioned multifunctional high magnetic particle content resin film in a composite material product.
[0042] The present invention realizes the preparation of a multifunctional resin film with a high magnetic particle content by the following technical scheme:
[0043] A specific implementation of a multifunctional resin film with high magnetic particle content is as follows: the multifunctional resin film with high magnetic particle content is composed of a resin film with high magnetic particle content, a fiber film attached to the surface of the film, or a functional film attached to the surface of the film and covering the fiber film. The volume percentage of magnetic filler in the resin film is 40-75%; the pure resin in the resin film is epoxy resin or bismaleimide resin, the minimum viscosity of the pure resin is lower than 40 Pa.s, and the gel time at this viscosity is at least higher than 20 minutes; the thickness of the fiber film is between 1 and 200 μm, the thickness-to-diameter ratio is ≥10, and the porosity is higher than 40%.
[0044] The preparation method is as follows: a resin film with a relatively low magnetic filler content is sequentially laminated with a fiber film or a functional film covering the fiber film and a glue absorbing film, and then glue absorbing is performed at a certain temperature and pressure, the viscosity of the resin at the glue absorbing temperature is lower than 40 Pa.s, the glue absorbing pressure is 0.04-1 MPa, the glue absorbing time is 1-40 minutes, and after the glue absorbing is completed, the glue absorbing film is removed, the viscosity of the pure resin at the film removal temperature is lower than 40 Pa.s, or it is removed at room temperature in the presence of a porous anti-adhesive film. The volume percentage of the magnetic filler in the resin film with a relatively low magnetic filler content is 30-40%, and the thickness is lower than 1.5 mm.
[0045] The beneficial effects of this application include:
[0046] 1) The multifunctional high magnetic particle content resin film provided by the present invention uses a functional membrane with a specific structure as a filter layer and composites it with a magnetic film, innovatively making full use of its structural characteristics, combined with an easily peelable external absorbing material, to achieve an absorbing resin film with an ultra-high magnetic particle content that is difficult to prepare by conventional methods, and at the same time achieves multifunctional superposition and mutual promotion of the film, achieving the functionality of the film material of 1+1>2.
[0047] 2) The present invention aims at the problem that the prior art is difficult to achieve with respect to the resin film having an extremely high magnetic particle content. The present invention innovatively adopts a glue filtering and glue suction method to achieve the preparation of a multifunctional resin film material having a high magnetic particle content.
[0048] 3) The present invention also provides a method for preparing a resin film with an extremely high magnetic particle content and having more functionality, so that the multifunctional resin film with a high magnetic particle content can meet more functional requirements and obtain additional significant effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0050] Figure 1 This is a schematic diagram of the composition of the multifunctional high magnetic particle content resin film in this application;
[0051] Figure 2 This is a graph showing the variation trend of the half-absorption time with the resin viscosity and the film thickness in this application;
[0052] Figure 3 This is a graph showing the variation trend of the half-absorption time with the porosity and film thickness in this application. DETAILED DESCRIPTION
[0053] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] In order to achieve the technical purpose of the present invention, the present invention innovatively proposes a new solution, that is, a resin film with a high magnetic particle content is obtained by a glue suction method, while retaining a filter layer as a functional layer, thereby realizing the preparation of a multifunctional resin film with a high magnetic particle content. In order to realize this solution, a porous fiber membrane or a functional membrane covering a fiber membrane attached to the surface of a low magnetic particle resin film is selected as a filter layer to prevent the magnetic filler from migrating with the resin during the glue suction process. Compared with other porous materials, this fiber membrane has a higher ability to penetrate the resin, can achieve good glue penetration, and improve production efficiency.
[0055] The present invention needs to solve the following problems: (1) good glue permeability; (2) good glue filtering performance; (3) easy-to-remove glue absorption membrane.
[0056] (1) Good adhesive permeability is achieved by controlling the resin viscosity and the porosity of the fiber membrane.
[0057] Although the resin mixed with a high content of magnetic particles has a very high viscosity, the pure resin can still be separated from the mixture under pressure. Therefore, the effective half-absorption time t is established as a parameter to evaluate the resin's ability to penetrate the glue. The so-called half-absorption time is the time required for the glue penetration to reach half of the maximum glue output. It is related to factors such as resin viscosity, glue suction pressure, glue suction temperature, glue film thickness, initial magnetic particle content, and fiber membrane characteristics such as porosity. Therefore, there are two main controlling factors during glue suction: (a) the flow ability in the glue layer; (b) the flow ability in the fiber membrane. For (a), a high-porosity fiber membrane (porosity of about 70%), the most commonly used resin with magnetic particle content (38 vol%, flaky carbonyl iron powder), and pure resins of different viscosities were used as research objects. The typical glue suction pressure used was 0.1 MPa. The change of t with the change of resin viscosity and glue film thickness can be seen. Figure 2 It can be seen that t increases rapidly with the increase of resin viscosity, especially after a long outflow time, the resin solidification degree increases, the viscosity is greater, and it is difficult to flow out. At the same time, the increase in thickness also leads to a smaller applicable viscosity range. Therefore, in specific operations, the viscosity of the pure resin should be controlled to be lower than 40Pa.s, and the thickness of the film should be lower than 1.5mm. Preferably, the viscosity of the pure resin is lower than 20Pa.s, and the thickness of the film is lower than 1.5mm, which can meet most needs.
[0058] For the main control factor (b), the porosity of the fiber membrane was changed by impregnating and curing the fiber membrane with different amounts of resin. The typical pure resin viscosity (2Pa.s) and the most commonly used magnetic particle resin (38vol%, flaky carbonyl iron powder) were selected as the research objects. The typical suction pressure was 0.1MPa. The change of t with porosity and film thickness is shown in Figure 2. Figure 3When the porosity is high, t is basically affected by the internal flow of the adhesive layer, but when the porosity is lower than 40%, t increases rapidly, indicating that the internal flow channel is blocked, so the porosity of the fiber membrane should be controlled above 40% in practical applications.
[0059] (2) For the realization of filterability, the thickness-diameter ratio of the fiber membrane and the diameter of the fiber are the most important influencing factors. For nanofiber membranes, when the membrane layer is sufficiently complete, the ratio of the membrane layer thickness to the fiber diameter is generally much greater than 10, and the pore size is lower than that of the magnetic particle filler. Generally, magnetic particles will not penetrate. In order to avoid damage under pressure, its thickness should not be less than 1μm, even if it is attached to the surface of the functional layer. For micron fiber membranes, the penetration of magnetic particles from the pores must be considered. The relationship between the penetration and the thickness-diameter ratio of the fiber membrane and the fiber diameter is shown in Table 1. In Table 1, the magnetic nanoparticles are flaky carbonyl iron powder, the volume fraction of flaky carbonyl iron powder in the film is 38 vol%, the film thickness is 0.5 mm, and the pure resin viscosity is 2 Pa.s at the test temperature. As can be seen from Table 1, when the fiber diameter becomes smaller, the pores formed by the overlap become smaller, and the anti-magnetic penetration ability is significantly enhanced. However, when the thickness-diameter ratio is smaller, the membrane layer strength is too low and damage occurs, resulting in the penetration of magnetic particles from the damaged position. Therefore, the preferred thickness-to-diameter ratio is ≥10, and the fiber diameter is further preferably ≤5 μm. The fiber membrane thickness is 5 to 200 μm. For fiber membranes supported by functional layers that are not easily damaged, the preferred minimum thickness is 1 μm.
[0060] Table 1. Magnetic particle penetration in fiber membranes with different fiber diameters and thickness-to-diameter ratios
[0061]
[0062] (3) Easy-to-remove adhesive film. Studies have shown that when the resin viscosity is controlled to be ≤40 Pa.s in (1), the adhesive film can be easily removed at this viscosity. Preferably, a porous anti-adhesive film such as polytetrafluoroethylene cloth, polytetrafluoroethylene porous film, etc. can be added between the adhesive film and the filter membrane / functional membrane, so that the adhesive film can be removed at room temperature and the anti-adhesive film can be retained as a protective functional layer.
[0063] After research, a technical solution for a resin film with high magnetic particle content and good permeability, filterability and film peeling properties has been realized. According to application requirements, a multifunctional fiber membrane can be used as a filter membrane, such as a carbon nanotube membrane, a carbon nanofiber membrane, a highly toughened nano non-woven fabric, a highly toughened melt-blown fabric, etc., preferably with a fiber diameter of ≤5μm and a thickness of 5 to 50μm. It is also possible to attach a preferably thinner fiber membrane to the surface of the functional membrane to achieve permeability, filterability and multifunctionality, wherein the functional membrane is preferably a metal-plated non-woven fabric with a surface resistance of ≤0.05Ω, a thickness of 10 to 100μm, and a pore size of less than 20μm; or the functional membrane is a smooth film containing holes, and the diameter of the holes is ≤2mm; or the functional membrane is a porous resistive film with a thickness of 5 to 100μm; and at this time, the fiber diameter of the fiber membrane is ≤5μm and the thickness is 5 to 50μm.
[0064] (4) In addition, when the adhesive absorption layer is made of plain glass fiber cloth or breathable demoulding cloth (such as polytetrafluoroethylene demoulding cloth), the plain glass fiber cloth or breathable demoulding cloth can even absorb adhesive during the composite material molding process, and be peeled off after molding and cooling, so the process of intermediate adhesive absorption and removal of the adhesive absorption layer is omitted. The principle is that after the plain glass fiber cloth or breathable demoulding cloth is impregnated and solidified, it is easy to be peeled off from the surface of the composite material through interlayer opening tearing. The design principle of this method is consistent with the technical solution of the adhesive absorption and adhesive layer removal steps, that is, both are achieved through the designed functional fiber membrane's adhesive filtering and the adhesive absorption of the adhesive absorption layer.
[0065] The following is an exemplary description of the preparation method of the multifunctional high magnetic particle content resin film of the present invention. Figure 1 The figure shows a schematic diagram of the composition of the multifunctional resin film with high magnetic particle content prepared in an embodiment of the present invention, wherein a low magnetic particle content film, a functional fiber film or a functional film covering a fiber film and an adhesive absorption film are sequentially laminated, and after hot pressing and adhesive absorption, the adhesive absorption film is peeled off to prepare a multifunctional resin film with high magnetic particle content.
[0066] Example 1
[0067] The implementation process of the technical solution of this embodiment is as follows:
[0068] (1-1) Take an epoxy resin film with a relatively low magnetic filler content, wherein the epoxy resin curing agent is DDS, the curing temperature is 180°C, and the viscosity of pure epoxy resin is 1.2 Pa.s at 120°C; the magnetic filler is flake carbonyl iron powder, and the content is 75wt% (31.4vol%); the film thickness is 0.3mm;
[0069] (1-2) The resin film with low magnetic particle content is laminated with nylon 66 nanofiber film and adhesive felt in sequence through an adhesive film laminating machine, wherein the nylon 66 nanofiber film has a thickness of 15 μm, a fiber diameter of 55 nm, and an aspect ratio of 273, and the adhesive felt is made of plain glass fiber cloth with a thickness of 215 μm, and then slowly passed through a hot rolling roller, the temperature of the hot rolling roller is 120°C, the hot rolling pressure is 0.1 MPa, and the laminating hot rolling time is controlled to be 3 min;
[0070] (1-3) After the composite film is passed through a hot rolling roller, it is passed through a film peeling machine at a film peeling temperature of 120°C to peel off the adhesive felt, retain the nanofiber film, and then wound to obtain a multifunctional high magnetic particle content resin film, the magnetic particle content is increased to about 89wt% (55.3vol%), and the total thickness of the composite film is reduced to 0.18mm;
[0071] (1-4) Take carbon fiber prepreg CCF800 / 1316, cut it into 8 sheets of 600mm×600mm in size and oriented at 0° and 45°, and then lay it in quasi-isotropic manner. After the laying is completed, lay 1 layer, 5 layers or 10 layers of the resin film with high magnetic particle content containing nanofiber film on the surface obtained above, and co-curing to obtain a multifunctional structural composite material.
[0072] The volume fraction of magnetic particles in the resin layer of the resin film with high magnetic particle content obtained above reaches 55.3% (mass fraction is 89wt%). When containing the same magnetic particles, the weight of a single-layer magnetic resin film is reduced by 150g / m 2 For laying 10 layers of magnetic film with a total thickness of about 2mm, the weight reduction is up to 1500g / m 2 The interface of multi-layer paving of the adhesive film or paving with the matrix composite material has good bonding force. The tensile shear strength of the co-cured structure of the film and the composite material is 27.3MPa, while when the adhesive film with low magnetic particle content is co-cured, the tensile strength is only 16.2MPa, indicating that the introduction of the nanofiber membrane significantly improves the bonding strength and the crack resistance of the magnetic layer, achieving the multifunctionality of wave absorption and high toughness.
[0073] Example 2
[0074] The implementation process of the technical solution of this embodiment is as follows:
[0075] (2-1) Take an epoxy resin film with a relatively low magnetic filler content, wherein the epoxy resin curing agent is DDS, the curing temperature is 180°C, and the viscosity of pure epoxy resin is 2.3 Pa.s at 120°C; the magnetic filler is spherical carbonyl iron powder, and the content is 78wt% (35.1vol%); the film thickness is 0.5mm;
[0076] (2-2) laminating a resin film with a low magnetic particle content with a carbon nanotube film and a glue-absorbing felt in sequence through a film laminating machine, wherein the carbon nanotube film has a thickness of 150 μm and an aspect ratio of 15000, and the glue-absorbing felt is a nylon non-woven felt with a thickness of 140 μm, and then applying pressure to the film by vacuum bag pressing, the bag pressing temperature is 120° C., and the laminating time is controlled to be 30 min;
[0077] (2-3) After the bagging is completed, the composite film with the adhesive felt is taken out, the adhesive felt is peeled off at 100° C., the carbon nanotube film is retained, and then wound to obtain a multifunctional resin film with a high magnetic particle content, the magnetic particle content is increased to about 91 wt % (60.6 vol %), and the total thickness of the composite film is reduced to 0.28 mm;
[0078] (2-4) Take carbon fiber prepreg CCF800 / 1316, cut it into 8 sheets of 600mm×600mm in size and oriented at 0° and 45°, and then lay it in quasi-isotropic manner. After the laying is completed, lay 1 or 3 layers of the resin film with high magnetic particle content containing nanofiber film on the surface obtained above, and co-curing to obtain a multifunctional structural composite material.
[0079] (2-5) The above carbon nanotube membrane can also be changed into a nanocarbon fiber membrane. The nanocarbon fiber membrane has a thickness of 200 μm, a fiber diameter of 75 nm, an aspect ratio of 2670, and is bonded into a whole using polyimide.
[0080] (2-6) The carbon nanotube film can also be replaced with buckypaper, which has a thickness of 120 μm, a fiber diameter of 10 nm, an aspect ratio of 12000, and is bonded into a whole using polyimide.
[0081] The volume fraction of magnetic particles in the resin layer of the resin film with high magnetic particle content obtained above reaches an astonishing 60.6 vol% (mass fraction is 91 wt%). The obtained composite material board has multifunctional properties such as wave absorption, lightning resistance, and high electromagnetic shielding. The composite material can resist lightning strikes in the 2A zone. After being struck by simulated lightning in the 2A zone, its damage level is equivalent to that of conventional copper mesh protection, but its shielding effectiveness reaches 105 dB, which is much higher than the 78 dB of ordinary composite materials with copper mesh protection. After using the high magnetic particle layer film, the weight of the resin in the film is reduced by 265 g / m 2 The weight reduction is considerable, and the presence of the carbon nanotube film also acts as a reflective layer, eliminating the need for a highly conductive reflective layer, further improving the weight reduction. The composite material containing the highly magnetic nanoparticle functional layer can be further designed through electromagnetic structure to achieve high absorption of the composite material and low weight.
[0082] Example 3
[0083] The implementation process of the technical solution of this embodiment is as follows:
[0084] (3-1) A bismaleimide resin film with a relatively low magnetic filler content is prepared, wherein the curing temperature of the bismaleimide resin is 180°C, the post-curing temperature is 200°C, and the viscosity of the pure bismaleimide resin is 0.15 Pa.s at 120°C; the magnetic filler is flaky carbonyl iron powder, and the content is 80 wt% (37.9 vol%); the film thickness is 0.8 mm;
[0085] (3-2) The resin film with low magnetic particle content is laminated with an anti-lightning film (thickness 25 μm, surface resistance 0.008 Ω, porosity about 50%, pore size 5 μm), a nanofiber membrane (fiber diameter 57 nm, thickness 12 μm, thickness-diameter ratio 2:11), and a glue felt in sequence through a film laminating machine, wherein the nylon 66 nanofiber membrane has a thickness of 15 μm, and the glue felt is made of polytetrafluoroethylene release cloth with a thickness of 100 μm and 5 layers (total thickness 500 μm), and then slowly passed through a hot rolling roller, the temperature of the hot rolling roller is 120°C, the hot rolling pressure is 0.2 MPa, and the lamination hot rolling time is controlled to be 18 min;
[0086] (3-3) After the composite film is passed through a hot rolling roller, it is passed through a film peeling machine at a film peeling temperature of 120°C to peel off the adhesive felt, retain the nanofiber film, and then wound to obtain a multifunctional high magnetic particle content resin film, the magnetic particle content is increased to about 90 wt% (57.8 vol%), and the total thickness of the composite film is reduced to 0.5 mm;
[0087] (3-4) The composite film can also be cooled to room temperature to remove the polytetrafluoroethylene release cloth. The resin viscosity at room temperature is 872 Pa.s, and the polytetrafluoroethylene release cloth can be removed well, and the multifunctional high magnetic particle content film layer has no obvious damage;
[0088] (3-5) taking carbon fiber prepreg CCF800 / QY9611, cutting the material to obtain 8 sheets of prepreg with a size of 600 mm×600 mm and an orientation of 0° and 45°, and then quasi-isotropically laying the layers, and after the laying is completed, laying a layer of the resin film with a high magnetic particle content containing a nanofiber film on the surface obtained above on the surface, and co-curing to obtain a multifunctional structural composite material;
[0089] (3-6) After the resin film with low magnetic particle content in (3-2) is laminated with the lightning protection film, nanofiber film and adhesive felt (polytetrafluoroethylene release cloth) in sequence through an adhesive film laminating machine, it can be directly laminated with the prepreg in (3-5) without pre-pressing adhesive, and adhesive is absorbed under the molding process, co-cured and cooled to room temperature, and then the adhesive-absorbing and cured polytetrafluoroethylene release cloth is removed to obtain a multifunctional structural composite material;
[0090] (3-7) The combination of the lightning protection membrane and the nanofiber membrane in (3-2) above can also be replaced by a single nanofiber lightning protection membrane, which is obtained by chemically plating metallic silver on the surface of the nanofiber membrane. The final membrane has a fiber diameter of 57nm, a thickness of 16μm, and a thickness-to-diameter ratio of 281.
[0091] The volume fraction of magnetic particles in the resin layer of the resin film with high magnetic particle content obtained above reaches 57.8 vol% (mass fraction is 90 wt%), which is much higher than the magnetic resin film obtained by conventional methods (the limit under the process requirements is about 82 wt%), and the weight reduction per unit area reaches 320 g / m 2 At the same time, the resin film with high magnetic particle content used in composite materials also has good lightning resistance, which can resist lightning strikes in zone 2A, and there is almost no visible surface fiber damage.
[0092] Example 4
[0093] The implementation process of the technical solution of this embodiment is as follows:
[0094] (4-1) Take an epoxy resin film with a relatively low magnetic filler content, wherein the epoxy resin curing agent is dicyandiamide, the curing temperature is 180°C, the viscosity of pure epoxy resin at 100°C is 11.6 Pa.s, and the viscosity at room temperature is 895 Pa.s; the magnetic filler is spherical carbonyl iron powder, the content is 78wt% (35.1vol%); the film thickness is 0.6mm;
[0095] (4-2) The resin film with low magnetic particle content is sequentially laminated with a high-temperature resistant nylon 66 melt-blown film, an anti-adhesive film (porous smooth polycarbonate film or polytetrafluoroethylene cloth), and a glue-absorbing felt using a hot iron, wherein the high-temperature resistant nylon 66 melt-blown film has a thickness of 45 μm, a fiber diameter of 2.5 μm, and an aspect ratio of 18, and the glue-absorbing felt is a low-cost polyester fiber non-woven felt with a thickness of 230 μm. Then, a vacuum bag is used for glue absorption treatment at 100°C, the vacuum bag pressure is 0.1 MPa, and the lamination glue absorption time is controlled to be 50 min;
[0096] (4-3) After the glue suction is completed, the mixture is cooled to room temperature, the anti-adhesive film and the glue suction felt are peeled off, and the nanofiber membrane is retained, or only the glue suction felt is peeled off, and the nanofiber membrane is retained as a functional layer and the anti-adhesive film is used as a protective layer, thereby obtaining a multifunctional resin film with a high magnetic particle content, wherein the magnetic particle content is increased to about 86 wt % (48.4 vol %), and the total thickness of the composite film is reduced to 0.44 mm (including the fiber membrane);
[0097] (4-4) Take carbon fiber prepreg CCF800 / 5228, cut it into 8 sheets of 600mm×600mm in size and oriented at 0° and 45°, and then lay it in quasi-isotropic manner. After the laying is completed, lay 1 layer, 3 layers or 5 layers of the resin film with high magnetic particle content containing fiber film on the surface obtained above, and co-curing to obtain a multifunctional structural composite material.
[0098] The volume fraction of magnetic particles in the resin layer of the resin film with high magnetic particle content obtained above is 48.4% (mass fraction is 86wt%). When containing the same magnetic particles, the weight of the single-layer magnetic resin film is reduced by 180g / m 2 For laying 5 layers of magnetic film with a total thickness of about 2.2mm, the weight reduction is up to 900g / m 2 The interface of the multilayer paving of the adhesive film or the paving with the matrix composite material has good bonding strength. The tensile shear strength of the co-cured structure of the film and the composite material is 51.4MPa, while when the adhesive film with low magnetic particle content is co-cured, the tensile strength is only 27.5MPa, indicating that the introduction of the fiber membrane significantly improves the bonding strength and realizes the multifunctionality of wave absorption and high toughness.
[0099] Example 5
[0100] The implementation process of the technical solution of this embodiment is as follows:
[0101] (5-1) A bismaleimide resin film with a relatively low magnetic filler content is prepared, wherein the curing temperature of the bismaleimide resin is 180°C, the post-curing temperature is 200°C, the viscosity of the pure bismaleimide resin is 0.15 Pa.s at 120°C, and the viscosity is 0.97 Pa.s at 100°C; the magnetic filler is flaky carbonyl iron powder, the content of which is 80 wt% (37.9 vol%); the film thickness is 0.8 mm;
[0102] (5-2) The resin film with low magnetic particle content is laminated with glass fiber cloth with nanofiber membrane formed by carbon nanotubes on the surface and adhesive felt in sequence through an adhesive film laminating machine, wherein the glass fiber cloth with nanofiber membrane formed by carbon nanotubes on the surface has a thickness of 95 μm, the carbon nanotube layer on it is 5 μm, the carbon nanotube layer resistance is 67 Ω / sq., the diameter of the carbon nanotube is 12 nm, that is, the thickness-to-diameter ratio of the carbon nanotube layer is 4:17, and the adhesive felt is made of ordinary alkali-free glass fiber plain weave cloth, the single layer thickness is 100 μm, and a total of 6 layers of adhesive are stacked (total thickness 600 μm), and then slowly passed through a hot rolling roller, the temperature of the hot rolling roller is 100°C, the hot rolling pressure is 0.15 MPa, and the lamination hot rolling time is controlled to be 15 min;
[0103] (5-3) After the composite film is passed through a hot rolling roller, it is passed through a film stripping machine at a film stripping temperature of 120°C to remove all the adhesive felts, leaving the glass fiber cloth with the carbon nanotube nanofiber film attached, and then winding to obtain a multifunctional high magnetic particle content resin film, the magnetic particle content is increased to about 90 wt% (57.9 vol%), and the total thickness of the composite film is reduced to 0.6 mm;
[0104] (5-4) Take carbon fiber prepreg CCF800 / QY9611, cut it into 8 sheets of 600 mm × 600 mm in size and oriented at 0° and 45°, and then lay it in quasi-isotropic manner. After the laying is completed, lay a layer of the resin film with high magnetic particle content obtained above on the surface, and co-curing to obtain a multifunctional structural composite material.
[0105] (5-5) The resin film with low magnetic particle content in the above (5-2) is laminated with glass fiber cloth with nanofiber film formed by carbon nanotubes on the surface and adhesive felt (ordinary alkali-free glass fiber plain cloth) in sequence through a film laminating machine, and then can be directly layered with the prepreg in (5-4) without pre-pressing adhesive, and adhesive is absorbed under the molding process. After co-curing and cooling to room temperature, the ordinary alkali-free glass fiber plain cloth that has been absorbed and cured is peeled off one by one to obtain a multifunctional structural composite material with a surface layer having a functional layer with high magnetic particle content and a carbon nanotube conductive layer with a certain resistance distributed on the glass fiber cloth carrier.
[0106] The volume fraction of magnetic particles in the resin layer of the resin film with high magnetic particle content obtained above reaches 57.9 vol% (mass fraction is 90 wt%), and the weight loss of a single layer reaches about 250 g / m 2 The film contains a carbon nanotube layer with good conductivity (surface resistance of 67Ω / sq.), and the introduction of electrodes on the composite material board can achieve the functions of wave absorption and electrical heating at the same time.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A multifunctional resin film with high magnetic particle content, characterized in that: The multifunctional resin film with high magnetic particle content comprises a wave absorbing layer and a filter layer attached to the surface of the wave absorbing layer; The wave absorbing layer is a film containing highly magnetic particles; The filter layer is selected from fiber membrane I and / or fiber membrane II-functional membrane; The functional membrane in the fiber membrane II-functional membrane covers the fiber membrane II; The volume percentage of magnetic particles in the multifunctional resin film with high magnetic particle content is 40-75%.
2. The multifunctional high magnetic particle content resin film according to claim 1, characterized in that: The pure resin in the multifunctional high magnetic particle content resin film is selected from at least one of epoxy resin and bismaleimide resin; The thickness of the fiber membrane I is 5 to 200 μm; The thickness-to-diameter ratio of the fiber membrane I is ≥10, and the porosity is higher than 40%.
3. The multifunctional high magnetic particle content resin film according to claim 1, characterized in that: The thickness of the fiber membrane II in the fiber membrane II-functional membrane is 1 to 200 μm; The thickness of the fiber membrane II in the fiber membrane II-functional membrane is 5 to 50 μm; The fiber diameter of the fiber membrane II is ≤5 μm; The fiber membrane I and fiber membrane II are independently selected from at least one of carbon nanotube membrane, carbon nanofiber membrane, high-toughened nano non-woven fabric, high-toughened melt-blown fabric, and melt-blown micron fiber membrane.
4. The multifunctional high magnetic particle content resin film according to claim 1, characterized in that: The functional membrane in the fiber membrane II-functional membrane is selected from at least one of metal-plated non-woven fabrics, smooth films containing holes, and porous resistor films; The functional membrane is a metal-plated non-woven fabric with a surface resistance of ≤0.05Ω, a thickness of 10 to 100 μm, and a pore size of less than 20 μm; The functional film is a smooth film containing holes, and the diameter of the holes is ≤2mm; The functional film is a porous resistor film with a thickness of 5 to 100 μm.
5. The method for preparing a multifunctional resin film with a high magnetic particle content according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The low magnetic particle resin film is sequentially attached to the filter layer and the adhesive absorption layer, and then adhesive absorption is performed. After the adhesive absorption is completed, the adhesive absorption layer is removed to obtain a multifunctional resin film with high magnetic particle content.
6. The preparation method according to claim 5, characterized in that: The volume percentage of magnetic particles in the low magnetic particle resin film is 30-40%; The thickness of the low magnetic particle resin film is less than 1.5 mm; The magnetic particles in the low-magnetic particle resin film are selected from flaky carbonyl iron powder and / or spherical carbonyl iron powder.
7. The preparation method according to claim 5, characterized in that: The adhesive absorbing layer is selected from at least one of organic fiber felt, glass fiber cloth, and breathable release cloth; The thickness of the adhesive absorption layer is 100 to 700 μm; When the adhesive absorbing layer is selected from plain glass fiber cloth and / or breathable demoulding cloth, after the low magnetic particle resin film is sequentially laminated with the adhesive filter layer and the adhesive absorbing layer, the steps of adhesive absorbing and removing the adhesive absorbing layer are omitted, and the adhesive absorbing layer is directly used for laying and co-curing together with the prepreg of the composite material. After curing and molding, the co-cured adhesive absorbing layer is torn off through interlayer separation.
8. The preparation method according to claim 5, characterized in that: During the glue suction, the viscosity of the pure resin in the low magnetic particle resin film at the glue suction temperature is lower than 40 Pa.s; The pressure of the glue suction is 0.04-1MPa; The time of the glue suction is 1 to 60 minutes.
9. The preparation method according to claim 5, characterized in that: The adhesive absorbing layer is removed by peeling off the adhesive absorbing layer through a film peeling machine.
10. Use of the multifunctional resin film with high magnetic particle content as claimed in any one of claims 1 to 4 in composite products.
Citation Information
Patent Citations
Multilayer wave-absorbing composite material and preparation method thereof
CN113400736A
Resistant diaphragm for electromagnetic wave
CN2569536Y